Scalable and reliable orchestration for balancing the workload among SDN controllers - Moura, J. (Proceedings of International Conference on Information Technology and Applications: ICITA 2022, 2023)
There is a high demand for Software Defined Networking (SDN) solutions to control emerging networking scenarios. Due to the centralized design of SDN, a single SDN controller could have its performance severely degraded due to workload congestion or even if it becomes out of service after being menaced by failures or cyber-attacks. To enhance the robustness and scalability of the control system level, it is fundamental for the deployment of multiple redundant controllers, which need to be correctly orchestrated for ensuring these controllers efficiently control the data plane. This work designs, deploys, and evaluates a new East/Westbound distributed light protocol, which supports the leaderless orchestration among controllers. This protocol is based on group communication over UDP. The evaluation results show the merits of the proposed orchestration design on the system scalability, workload balancing, and failure robustness.